Pore size measurements and distribution for ceramic membranes - Rahman, M. A. (Elsevier Inc., 2017)
This chapter discusses various methods in characterizing porous ceramic membranes. The fundamental theory and calculation for every approach are given to relate the basic concept of each technique to the results obtained from experiments. A number of techniques are discussed, including gas adsorption/desorption isotherm, permporometry, mercury porosimetry, thermoporometry, bubble point method, and liquid displacement technique. This chapter includes some step-by-step methodologies in obtaining the results of pore properties for ceramic membranes. The view and comparisons that include the advantages and limitations are given in the end of this chapter.